2019 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2019
DOI: 10.23919/date.2019.8715061
|View full text |Cite
|
Sign up to set email alerts
|

Bosphorus: Bridging ANF and CNF Solvers

Abstract: Algebraic Normal Form (ANF) and Conjunctive Normal Form (CNF) are commonly used to encode problems in Boolean algebra. ANFs are typically solved via Gröbner basis algorithms, often using more memory than is feasible; while CNFs are solved using SAT solvers, which cannot exploit the algebra of polynomials naturally. We propose a paradigm that bridges between ANF and CNF solving techniques: the techniques are applied in an iterative manner to learn facts to augment the original problems. Experiments on over 1,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…During the experiments, we found that if the ANF-to-CNF converter called Bosphorus [CSCM19] is used to convert the S-boxes, the performance may be improved in practice, which may be explained by its discovery implicit linearity and compression of the CNF formula. Bosphorus is an MIT-licensed open-source software, which is aimed at simplifying ANF-to-CNT conversion over GF (2).…”
Section: Evaluation Of Different Fault Modelsmentioning
confidence: 99%
“…During the experiments, we found that if the ANF-to-CNF converter called Bosphorus [CSCM19] is used to convert the S-boxes, the performance may be improved in practice, which may be explained by its discovery implicit linearity and compression of the CNF formula. Bosphorus is an MIT-licensed open-source software, which is aimed at simplifying ANF-to-CNT conversion over GF (2).…”
Section: Evaluation Of Different Fault Modelsmentioning
confidence: 99%
“…[15; 17; 16; 22; 21]. Recent work has also focused on combining algebraic and SAT solving techniques [7]. In public key cryptography, SAT solvers have been considered for attacking binary elliptic curve cryptosystems using the index calculus attack [13].…”
Section: Introductionmentioning
confidence: 99%